Prognostic Awareness and Goals of Care Discussions Among Patients With Advanced Heart Failure. (September 2020) - Gelfman, Laura P.; Sudore, Rebecca L.; Mather, Harriet; McKendrick, Karen; Hutchinson, Mathew D.; Lampert, Rachel J.; Lipman, Hannah I.; Matlock, Daniel D.; Swetz, Keith M.; Pinney, Sean P.; Morrison, R. Sean; Goldstein, Nathan E.
Abstract : Background: Prognostic awareness (PA)—the understanding of limited life expectancy—is critical for effective goals of care discussions (GOCD) in which patients discuss their goals and values in the context of their illness. Yet little is known about PA and GOCD in patients with advanced heart failure (HF). This study aims to determine the prevalence of PA among patients with advanced HF and patient characteristics associated with PA and GOCD. Methods: We assessed the prevalence of self-reported PA and GOCD using data from a multisite communication intervention trial among patients with advanced HF with an implantable cardiac defibrillator at high risk of death. Results: Of 377 patients (mean age 62 years, 30% female, 42% nonwhite), 78% had PA. Increasing age was a negative predictor of PA (odds ratio, 0.95 [95% CI, 0.92–0.97]; P <0.01). No other patient characteristics were associated with PA. Of those with PA, 26% had a GOCD. Higher comorbidities and prior advance directives were associated with GOCD but were of only borderline statistical significance in a fully adjusted model. Symptom severity (odds ratio, 1.77 [95% CI, 1.19–2.64]; P =0.005) remained a robust and statistically significant positive predictor of having a GOCD in the fully adjusted model. Conclusions: In a sample of patients with advanced HF, the frequency of PA was high, but fewer patients with PA discussed their end-of-life care preferences with their physician. Improved efforts are needed to ensure all patients with advanced HF have an opportunity to have GOCD with their doctors. Clinicians may need to target older patients with HF and continue to focus on those with signs of worsening illness (higher symptoms). Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01459744. Abstract : Supplemental Digital Content is available in the text.